Atomic Layer Deposition of a Silver Nanolayer on Advanced Titanium Orthopedic Implants Inhibits Bacterial Colonization and Supports Vascularized de Novo Bone Ingrowth. Issue 11 (21st March 2017) - Devlin‐Mullin, Aine; Todd, Naomi M.; Golrokhi, Zahra; Geng, Hua; Konerding, Moritz A.; Ternan, Nigel G.; Hunt, John A.; Potter, Richard J.; Sutcliffe, Chris; Jones, Eric; Lee, Peter D.; Mitchell, Christopher A.
Abstract : Joint replacement surgery is associated with significant morbidity and mortality following infection with either methicillin‐resistant Staphylococcus aureus (MRSA) or Staphylococcus epidermidis . These organisms have strong biofilm‐forming capability in deep wounds and on prosthetic surfaces, with 10 3 –10 4 microbes resulting in clinically significant infections. To inhibit biofilm formation, we developed 3D titanium structures using selective laser melting and then coated them with a silver nanolayer using atomic layer deposition. On bare titanium scaffolds, S. epidermidis growth was slow but on silver‐coated implants there were significant further reductions in both bacterial recovery ( p < 0.0001) and biofilm formation ( p < 0.001). MRSA growth was similarly slow on bare titanium scaffolds and not further affected by silver coating. Ultrastructural examination and viability assays using either human bone or endothelial cells, demonstrated strong adherence and growth on titanium‐only or silver‐coated implants. Histological, X‐ray computed microtomographic, and ultrastructural analyses revealed that silver‐coated titanium scaffolds implanted into 2.5 mm defects in rat tibia promoted robust vascularization and conspicuous bone ingrowth. We conclude that nanolayer silver of titanium implants significantly reduces pathogenic biofilm formation in vitro, facilitates vascularization and osseointegration in vivo making this a promising technique for clinical orthopedic applications. Abstract : Atomic layer deposition is used to coat the surface of titanium foams with a silver nanolayer, resulting in 2‐log fold reduction of Staphylococcus epidermidis growth. Osteogenic cells, fibroblasts, and endothelium grow on these scaffolds in vitro. After implantation into rat tibia, vascular casting and scanning electron microscopy analysis (Etoc) reveal conspicuous bone ingrowth and numerous mature blood vessels on the struts.